Microsatellite Genetic Differentiation Analysis of Two Local Chicken Breeds Compared with Foreign Hy-Line Strain - Roushdy, Kh.; El-Dein, A. Zein; Fathi, M.M.; Ali, U.M.; Assy, Heba M. (International Journal of Poultry Science, 2008)
The present study was conducted on two Egyptian native breeds (Dandarawi and Fayoumi) and commercial laying hens (brown Hy-line) to estimate genetic differentiation using microsatellites and their association with egg production traits. Five microsatellite markers, four located on Z chromosome and one located on chromosome 1 were used in this study. The present results indicated that the Hy-line strain had significantly better egg production parameters and feed conversion ratio compared to two native breeds. Inversely, the two native breeds had better eggshell quality measurements compared to Hy-line hens. The five microsatellite genetic markers applied in the present study success to reveal high degree of polymorphism among the three breeds used here. Also, a clear discriminating power was achieved in differentiation among studied chicken populations. The genetic distance revealed that Fayoumi breed is mostly related to Hy-line strain more than Dandrawi breed.